Active trading strategies based on momentum and term structure signals in commodity futures market: evidence from India. (25th November 2020) - Jaiswal, Ritika
This research designs an active double-sort strategy which integrates both momentum and term structure signals present in the commodity futures market. By using a sample of highly traded commodity future contracts of the Indian commodity market from 2006 to 2016, this study confirms the exceptionally high abnormal profitability of the double-sort strategy. The abnormal returns of the double-sort portfolios are robust to transaction costs incurred for designing these active strategies. The application of a conditional multi-factor model and sub-sample analysis suggests that the return profile of these strategies is basically time-varying. Moreover, the low and insignificant correlation of double-sort portfolios with stocks and bonds confirms that relative strength portfolios of commodity futures can be effectively used to create a well-diversified portfolio.